INVESTIGATING THE CAUSES OF MOLAR INCISOR HYPOMINERALIZATION: A CROSS-SECTIONAL STUDY ON MATERNAL AND CHILD HEALTH FACTORS - Akgün, Özlem Martı (2024)
Objectives: This study aims to investigate the factors contributing to Molar Incisor Hypomineralization (MIH), with a focus on maternal health during pregnancy, delivery complications, and postnatal health and nutritional factors in children. Methods: A cross-sectional study was conducted involving detailed surveys completed by mothers regarding their health during pregnancy, delivery experiences, and their children's early health and nutritional history. Clinical examinations of the children were performed to diagnose MIH according to established criteria. Statistical analyses were conducted using IBM SPSS 29.0, including descriptive statistics and correlation analyses to identify associations between MIH and various maternal and child health factors. Results: The study found that 36.7% of mothers experienced illnesses during pregnancy, with gestational diabetes and hypertension being the most common conditions. Complications during delivery were observed in 3.3% of cases, and 16.7% of mothers had premature births. Common health issues in children included respiratory infections (26.7%), fever (23.3%), and otitis media (16.7%). Notably, dental defects were most prevalent in children with kidney disorders (66.7%), digestive system disorders (45.8%), and severe diarrhea (43.8%). Significant correlations were identified between MIH and these maternal and child health factors, highlighting the importance of comprehensive prenatal and postnatal care. Conclusion: The study underscores the multifactorial nature of MIH, revealing significant associations with maternal illnesses, delivery complications, and early childhood health issues. These findings emphasize the need for targeted preventive measures and early interventions to manage MIH effectively, particularly in children at higher risk due to compromised maternal or child health.